Optical and transport properties correlation driven by amorphous/crystalline disorder in InP nanowires. (23rd September 2016) - Kamimura, H; Gouveia, R C; Carrocine, S C; Souza, L D; Rodrigues, A D; Teodoro, M D; Marques, G E; Leite, E R; Chiquito, A J
Abstract: Indium phosphide nanowires with a single crystalline zinc-blend core and polycrystalline/amorphous shell were grown from a reliable route without the use of hazardous precursors. The nanowires are composed by a crystalline core covered by a polycrystalline shell, presenting typical lengths larger than 10 μ m and diameters of 80–90 nm. Raman spectra taken from as-grown nanowires exhibited asymmetric line shapes with broadening towards higher wave numbers which can be attributed to phonon localization effects. It was found that optical phonons in the nanowires are localized in regions with average size of 3 nm, which seems to have the same order of magnitude of grain sizes in the polycrystalline shell. Regardless of the fact that the nanowires exhibit a crystalline core, any considerable degree of disorder can lead to a localized behaviour of carriers. In consequence, the variable range hopping was observed as the main transport instead of the usual thermal excitation mechanisms. Furthermore the hopping length was ten times smaller than nanowire cross-sections, confirming that the nanostructures do behave as a 3D system. Accordingly, the V-shape observed in PL spectra clearly demonstrates a very strong influence of the potential fluctuations on the exciton optical recombination. Such fluctuations can still be observed at low temperature regime, confirming that the amorphous/polycrystalline shell of the nanowires affects the exciton recombination in every laser power regime tested.